Differences in Motivational Properties between Job Enlargement and Job Enrichment - Chung, Kae H.; Ross, Monica F. (Academy of Management Review, 1977)
Differences in motivational properties between job enlargement and job enrichment are investigated. Differences in employees' motivation and ability should be reflected in determining an appropriate type of job design. Expectancy/instrumentality theory of motivation provides a basis for explaining employees' responses to various job designs.